Refreshing China's Labor Education in the New Era: Policy Review on Education Through Physical Labor. (March 2020) - Fan, Guorui; Zou, Jiaxin
Purpose: This study reviews China's labor education theories and policies to reveal the main objectives, contents, and methods of the new era, as well as analyzes future development in labor education. Design/Approach/Methods: In addition to reviewing the relevant labor education theories, this study examines China's labor education policies using historical documents and current policy texts. Marxist and traditional approaches to labor education, as well as the historical development of education in China, provide the macroscopic backdrop of this study's analysis of the persistence and innovativeness of China's labor education policies. Findings: China's labor education policy has placed labor education on the same level as that in morality, intellect, sports, and aesthetics, thereby endowing labor education with new meaning. Labor education seeks to cultivate workers with all-round physical and mental development. Becoming more varied over time, labor education now involves the cultivation of skills, technological capacities, creative thinking, labor habits, and emotional development. Approaches and methods include formal programs and teaching, education in daily life at home and school, as well as practical activities outside of school. Originality/Value: This study identifies the meaning of labor education in different eras and analyzes the objectives, contents, and methods of China's current policies on labor education, as well as its future developmental trends. In doing so, this study provides a useful reference for the implementation of labor education in elementary and middle schools.